Perceptions on Halal food certification in Hat Yai, Thailand - Abdul, Mohani (Faculty of Economics and Management, Universiti Putra Malaysia, 2014)
This paper reports on the perceptions of Thailand Small and Medium Enterprises (SMEs) entrepreneurs towards Halal Food Certification (HFC) on three dimensions; market share and market competitiveness, government support and monitoring and Halal hub information dissemination. Based on responses from 98 respondents, the study found that it is important for Thailand SMEs to acquire HFC to promote customers’ confidence, trust and satisfaction but respondents raised dissatisfaction on the poor dissemination of Halal hub information. Hence, the agency involves in distributing information on Halal hub needs to improve its functional role of delivering information particularly on the quality of content, accessibility of media used and regularity of announcement. The study also indicates that respondents’ gender and marital status have significant influence on the intention to apply for Halal Certificate and the desire to obtain Halal Certification for their food products.